Exploring Differentiated Learning: A Bibliometric Examination of Research Development and Directions - Thayibah, Khamsah Ruhana; Salim, Hakimmuddin; Shohib, Muhammad Wildan; Maksum, Muh. Nur Rochim; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: To chart the progress and trajectory of differentiated learning research in Scopus database-indexed publications from 1954 - 2023. The first publication was found in 1994. Methodology: Using bibliometric analysis method. A literature review was performed to ensure that relevant research on bibliometric topics was conducted. A Boolean search engine was utilized to search the Scopus database from 1954 to 2023. The analysis of citations, document content, and networks was carried out using R and Rstudio tools, VosViewer, and Microsoft Excel. Using the Boolean operator TITLE-ABS-KEY (differentiated and learning) to search Scopus and generate 7,012 documents. Filtering is done with the Boolean operator (LIMIT-TO (SUBJAREA, "soci")) AND (LIMIT TO (DOCTYPE, "ar")) AND (LIMIT-TO (SRCTYPE, "j")) AND (LIMIT TO (LANGUAGE, "English")) for social science field restrictions, source documents are only journals and articles in English, resulting in 1. 425. analysis using Scopus, R, and Rstudio to determine the number of articles per year, per journal, author, affiliation, country, and topic/sector. To visualize using VOSviewer and Microsoft Excel data processing. Results: 848 publications matched the function, subject, and criteria set. Annual growth rate of 7.33%, most publications in 2022 by US country with affiliation from University of Toronto US. Jordan J was the most prolific author. Applications/Originality/Value: This bibliometric analysis is limited to Scopus data. Other national and international databases should have been considered in this study. This research offers a concise summary of the available literature for researchers engaged in differentiated learning and offers suggestions for future research endeavors.